First-principles study on the dissolution and diffusion behavior of hydrogen in carbide precipitates. (18th June 2021) - Li, Yifan; Zhang, Xingming; Wu, Tiantian; Tang, Jianfeng; Deng, Lei; Li, Wei; Wang, Liang; Deng, Huiqiu; Hu, Wangyu
Abstract: To understand the hydrogen (H) behavior in the carbide precipitates, the dissolution and diffusion properties of interstitial H in the transition metal carbide (TMC; TM = Hf, Nb, Ta, Ti, V, and Zr) were studied by first-principles calculations. In these carbides, it can be seen that H tends to occupy the trigonal site (tri2-site) surrounded by three transition metal atoms and one carbon atom rather than the face center (fc-site) and the body center (bc-site) which with the larger space. We found that the bonding interaction between H atom and the nearest-neighbor (1NN) carbon atom is the dominant influence on the stability of H dissolution. Besides, we obtained the temperature-dependent solubility and diffusion coefficients of H in TMC and pure vanadium through Sievert's law and transition state theory. Compared with pure vanadium, H shows the worse solubility in TMC, and it is more difficult for hydrogen to migrate in TMC, but segregate toward the interface. Furthermore, it is interesting to note that, the diffusion barrier and the H solution energy show a linear relationship for transition metal carbides in the same period. These results can help us deepen the understanding of H behavior in vanadium alloys strengthened by carbide precipitates, and furtherly providing the theoretical guidance for the design of alloys with excellent performance. Highlights: A DFT study about the dissolution and diffusion behavior of H in TMC was carried out. The site preference of H dissolve in the TMC is obtained. The linear relationship between solution energy and diffusion barrier is obtained. Compared with pure V, H is more difficult to dissolve in TMC. The stability of H in TMC dominates influence by bonding interaction.